Macunaíma (1978) de Antunes Filho: o olhar antropológico para a cena e a história brasileira - Barbosa, Kátia Eliane (2012)
This research, through the staging of Macunaíma, by Antunes Filho, in 1978, sought in the light of theoretical and methodological assumptions of Cultural History, seize the dialogue between arts and society, aesthetics and politics, history and theater and their contributions to the historiographical debate. In that perspective, looking into the theater produced by the director currently the coordinator of the Research Center of São Paulo Theatre enabled to view how engaged he was in the struggles of his time in favor of affirming national directors and the construction of a scenic language in Brazil. At a time when society lived under a state of exception, the \"leaden years\" marked by political persecution to the dissonant voices of the military regime, by will and restriction of cultural productions, the artist, through this historical context, resized his aesthetics language. Antunes s spectacle, by proposing a reflection on the character of Brazilian men, forms of consciousness and alienation, contributed to the modification of current theater parameters, marking the passage of a scene rooted in the verb to a scene based on the sign and which stands out the visual aspects. Considering the above, it was observed a refusal to politicized texts and the construction of a scene more and more aestheticized, in accordance with trends in contemporary theater. Thus, the formation work of the actor / creator considered the core element of the theater director from an internal path itself, based in the register consisting of the study of man and of Brazilian culture, was responsible for the outcome of a scene anthropological on stage at São Pedro Theater.